Dynamics of Oral Literature of the Moskona Tribe in the Current of Modernization: Between Preservation and Transformation - Nurnisaa; Okta, Setyo Luthfi (International Journal of Humanities, Law, and Politics, 2025)
Oral literature is an integral part of the culture of indigenous peoples, including the Moskona tribe in West Papua. This tradition plays a role in transmitting moral values, customary law, and the relationship between humans and nature. However, modernization brings changes in the pattern of delivery and sustainability of oral literature. This study aims to analyze the impact of modernization on the oral literature of the Moskona tribe and identify strategies for its preservation. Using a qualitative approach and ethnographic methods, data were collected through participatory observation, in-depth interviews, and documentation studies. The results of the study show that although the oral literature of the Moskona tribe still survives, the transmission pattern has changed from direct oral communication to written and digital documentation. The interest of the younger generation in oral delivery is starting to decline, with only 35% still actively listening to stories from traditional elders. In contrast, digital media such as videos, podcasts, and social media have become new means of spreading folklore. The preservation strategy involves various parties, including schools, local governments, cultural communities, and the younger generation, with efforts such as integration into the curriculum, cultural festivals, and digital documentation. This study confirms that modernization is not always a threat to oral literature, but can be an opportunity for its transformation and preservation. Further studies are needed to explore the effectiveness of digital strategies in maintaining the sustainability of oral traditions in indigenous communities.